2013
DOI: 10.2134/jeq2012.0126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Crop Rotation and Management System on Water‐Extractable Organic Matter Concentration, Structure, and Bioavailability in a Chernozemic Agricultural Soil

Abstract: Water-extractable organic matter (WEOM) in soil affects contaminant mobility and toxicity, heterotrophic production, and nutrient cycling in terrestrial and aquatic ecosystems. This study focuses on the influences of land use history and agricultural management practices on the water extractability of organic matter and nutrients from soils. Water-extractable organic matter was extracted from soils under different crop rotations (an annual rotation of wheat-pea/bean-wheat-flax or a perennial-based rotation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 113 publications
1
18
4
Order By: Relevance
“…For example, our results contrasts with a field study conducted in headwater catchments in Germany where agricultural practices led to the mobilization of more humified and aromatic DOM in streams compared to forest and wetland catchments (Graeber et al 2012). Similarly, waterextractable DOM from agricultural soils in Canada was found to be more chemically complex compared to forest and grassland soils (Xu et al 2013). In Australia, the reconversion of coastal wetlands for agricultural and urban purposes was without effects on stream DOM, the latter being characterized by a chemical composition typical of former wetland ecosystems (Petrone et al 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…For example, our results contrasts with a field study conducted in headwater catchments in Germany where agricultural practices led to the mobilization of more humified and aromatic DOM in streams compared to forest and wetland catchments (Graeber et al 2012). Similarly, waterextractable DOM from agricultural soils in Canada was found to be more chemically complex compared to forest and grassland soils (Xu et al 2013). In Australia, the reconversion of coastal wetlands for agricultural and urban purposes was without effects on stream DOM, the latter being characterized by a chemical composition typical of former wetland ecosystems (Petrone et al 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…Our result suggested that complex crop rotations release WEOM with higher aromaticity and humification. This is opposite to that of Xu et al [18] who reported the inclusion of a perennial crop alfalfa in a crop rotation, which releases WEOM with lower aromaticity and lower extent of humification. This may be attributed to simpler crop rotations in their study and different crop species they planted compared with our study.…”
Section: Spectroscopic Properties Of Weom and Relations To Soil Characontrasting
confidence: 95%
“…Reduced tillage and organic farming as alternative practices of conventional tillage and farming were reported to increase WEOC content by reducing soil disturbance and the addition of organic matter [11][12][13][14], while negative or neutral effect also existed [15][16][17][18]. However, most of the previous studies focused less on the quality of WEOM.…”
Section: Introductionmentioning
confidence: 99%
“…For these samples gravimetric soil moisture was quantified and this value was utilized to determine amount of water to add to field moist soils samples to ensure a 1:5 dry soil mass/ultrapure water volume for WERP extraction. Resulting soil water mixtures were shaken for 3 h, centrifuged at 4000 rpm to improve filtration, and then filtered with a 0.2 μm polycarbonate membrane filter prior to utilizing the ascorbic acid colourimetric method for determination of PO 4 -P in filtrates (Xu et al, 2013).…”
Section: Laboratory Analysismentioning
confidence: 99%